Jungermannia exertifolia Steph. - A new bryophyte record from Bangladesh (Dhaka University Journal of Biological Sciences, 2020)
A leafy liverwort, Jungermannia exertifolia Steph. (Hepaticae, Jungermanniales,) has been reported from the Adampur Forest of Moulvibazar district as a new species record for Bangladesh. Jungermannia exertifolia is characterized by its flattened leaves and rhizoids arising ventrally all along the stem with alternate leaves, which are obliquely inserted and succubous in arrangement. It grows in the shady habitats of Adampur forest on the surface of the hilly rocks. Detailed taxonomy of the newly reported species along with its photographs is provided.Dhaka Univ. J. Biol. Sci. 29(1): 133-136, 2020 (January)